News on Events and Social Media: A Comparative Analysis of Facebook Users’ Reactions - Salgado, Susana (2019)
Aiming to shed light on why Facebook users react to certain events and news stories more than to others, this study analyses their reactions to different events and to the media coverage of those events. The case selection includes six events covered by two newspapers from four countries: France, Italy, Portugal, and Spain. The research design combines an original content analysis of news media outlets’ posts with an analysis of the reactions that these posts have generated from Facebook users—likes, shares and comments—to assess whether and how the nature of events and the characteristics of the news content contribute to explaining the engagement of Facebook users with the news. The data analysis indicated that the decisions to like, share or comment were not driven by the same factors. Unexpected events showed significance, at different levels, for all kinds of reactions to news. Conversely, the specific features of news content only slightly affected the levels of liking and sharing. Facebook users were more likely to comment on news adhering to known criteria for news values, such as negativity or personalization.